تحاد العاقل والمعقول في فلسفة صدر الدين الشيرازي - رزيق, رابح (University of Eloued جامعة الوادي, 2020)
يهدف هذا البحث الى التعريف بمسألة اتحاد العاقل والمعقول، في فلسفة صدر الدين الشيرازي، وبيان طبيعتها وأصولها وأبرز البراهين والأدلة التي أقيمت لإثبات صحتها، وأهم الاعتراضات عليها، وهي من المسائل التي تدخل في سياق نظرية المعرفة في الفلسفة الإسلامية، كما يسعى البحث الى ابراز أهم الآثار والنتائج التي تترتب على القول بهذه المسألة، ومن ذلك إثبات علم الله بالأشياء، واتحاد العلم والعمل، والتأكيد على أن كل فرد من أفراد الإنسان هو نوع بحياله. The research it's aimed to introduce an matter of union the sane and the reasonable in the philosophy of Sadr al-Din al-Shirazi, clarified the nature, origins, the most proves and evidence that have been set up to prove its validity, and the most important objections of this matter, It is one of the matters that fall within the context of epistemology in Islamic philosophy, The research also seeks to highlight the most important effects and consequences of saying this matter, this includes proving God's knowledge of things, and union of knowledge and action, and the assertion that every individual of the human being is a kind about him.
Keywords: العاقل ; المعقول ; الاتحاد ; الحكمة المتعالية ; الفلسفة الإسلامية